The miniaturist - Burton, Jessie, 1982- (Ecco, an imprint of HarperCollinsPublishers, 2014)
Engaging the services of a miniaturist to furnish a cabinet-sized replica of her new home, 18-year-old Nella Oortman, the wife of an illustrious merchant trader, soon discovers that the artist's tiny creations mirror their real-life counterparts in eerie and unexpected ways.